The Influence of Product Quality on the Purchase Decision of MSME Products During the Covid-19 Pandemic - Heni Rohaeni; Muhammad Richo Rianto; Novita Wahyu Setyawati; Murti Wijayanti; Ganiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The research aims to determine how much product quality influences purchasing decisions for MSME products during the Covid 19 Pandemic. The method used in this research is quantitative descriptive, where this research is expected to provide an overview of the relationship between variables through testing using statistical calculations. The sampling technique used was purposive sampling with the help of data analysis methods namely validity test analysis, reliability test, correlation coefficient test, coefficient of determination test, and regression equation test. The number of respondents was 75 people. Based on the results of the study, it was found that the product quality variable had a positive and significant effect on the purchase decision variable. This shows that the influence between variables has a moderate positive dependency relationship category. While the results of the coefficient of determination show that there is a contribution from the product quality variable (X) to the purchasing decision variable (Y) of 33.7% and most of the remaining 66.3% is influenced by other factors not examined in this study